Partisipasi Masyarakat Dalam Mengelola Desa Wisata Wanagiri di Kabupaten Buleleng Untuk Memperkuat Ketahanan Ekonomi - Wiguna, I Putu Dhiva Sida Artha (Jurnal Penelitian Mahasiswa Indonesia, 2024)
Abstract This study aims to analyze: : 1) natural resources that can be developed especially in the tourism sector in Wanagiri Village; 2) local community participation in managing tourist villages and the impact of participation on the development of natural tourism in Wanagiri Village; 3) factors that become obstacles that affect participation in the management and development of natural tourism in Wanagiri Village. The type of research used is a qualitative research method with a research approach that emphasizes in-depth understanding and meaning of human, cultural, or environmental phenomena, using descriptive language and describing in detail the quality, context, and complexity of the phenomenon. The results of this study indicate the natural resources that can be developed especially in the tourism sector in Wanagiri Village are natural beauty such as waterfalls in Wanagiri Village. The participation of the Wanagiri Tourism Village community in managing existing natural tourism has become a very important guideline, this is useful for the smooth running of natural tourism management in Wanagiri Village. Obstacles in the management and development of natural tourism in Wanagiri Village include funds and facilities, human resources and accessibility are some forms of factors that are obstacles, this is an important role for the local community to continue to be improved so that it is useful for the smooth running of natural tourism management in the tourism sector.